A percepção e a ação docente: enfoques teórico-práticos decorrentes do uso das tecnologias de informação e comunicação (tic) na educação - Santos, Francisléia Giacobbo dos (2014)
Information technology and communication (ICT) has caused a revolution in the way people communicate, access information, perform everyday tasks, interact and seek knowledge; using equipment with internet access today, you can access any information on the desired topic. By means of digital technologies a new context arises even contributing to the advancement of scientific discoveries; this new environment also changes the way you live quickly and significantly, new listings, in interaction with different opinions and different views, provokes conflicts of ideas and values, changing society and ushering in new paradigms in different sectors making arise. In this perspective, and programs aimed at the integration of ICT in the school environment governmental actions began to emerge on the grounds that it is necessary to close the school reality from the reality experienced by society today; discussion about the use of technology in education is becoming ever harder, and with it, new educational paradigms are born and need to be researched. The present study aimed to understand the perceptions and teaching practices regarding the use of Information Technology and Communication (ICT) in teaching practices, using as a field of research, a group active in basic education teachers. The survey was developed through qualitative approach, exploratory. About the procedures, the present study used the documentary, bibliographical research and survey for data. Were selected as instruments for data collection: electronic questionnaire designs (learning objects) and semi-structured interviews. Data were analyzed according to content analysis (BARDIN, 2011). To reach the goal of the research, took to the observation and analysis, actions taken by the state to train teachers to use ICT and the perceptions and practices arising from participation in these programs that were tied to the State Department of Education (SEED) and the Ministry of Education (MEC). The subjects studied were the advisers of the Regional Coordinator of Educational Technology (CRTE), the Regional Center of Education of the City of Dois Vizinhos (PR) and teachers of Basic Education in public schools, participants in the training workshops conducted by CRTE, bound to the same NRE. The results indicate that teachers perceive ICT as an irreversible element in the school environment, aware of the need for training in the use of these technologies, but with qualification programs still far from pressing the daily school needs.